FRI0337 Tiarp Suppresses Migration of Neutrophils into Joints VIA Down-Regulation of CXCL2/CXCR2 Pathway in Autoimmune Arthritis. (10th June 2014) - Inoue, A.; Matsumoto, I.; Umeda, N.; Tanaka, Y.; Takai, C.; Kurashima, Y.; Takahashi, S.; Sumida, T.
Abstract : Background: TNFα-induced adipose-related protein (TIARP) is a six-transmembrane protein induced by TNFα and IL-6, and dominantly expressed in macrophages (Mϕ), neutrophils (Neu) and fibroblast-like synoviocytes (FLS). In human, TIARP is also observed in joints from patients with rheumatoid arthritis (RA) and clearly upregulated by TNFα stimulation. Recently, we found that TIARP functions as a negative regulator in autoimmune arthritis through the suppression of IL-6 production, NF-κB, STAT3 signaling in Mϕ, although the molecular mechanism of TIARP-expressing cells in arthritis remains uncertain. Objectives: The purpose of this study is to elucidate functional role of TIARP in the pathogenesis of arthritis, especially focusing on Neu and FLS. Methods: (1) We generated TIARP –/– mice and investigated several organs in aged mice (12-month-old). (2) We examined the susceptibility of TIARP –/– mice to collagen-induced arthritis (CIA), and screened the infiltrated cells into joints. (3) RNAs were extracted from TIARP –/– or WT Neu, and subsequently compared by Gene chip. (4) The expression of CXCR1, CXCR2, CCR1, and CCR3 on Neu was analyzed. (5) The expression of TIARP in FLS after TNFα, IL-6 and LPS were measured by qPCR. (6) Cell proliferation of FLS by TNFα stimulation was analyzed by BrdU incorporation. (7) Using WT or TIARP –/– FLS, the expression of IL-6, TNFα, CXCL2, RANKL, MMP3 and MMP9 after TNFα stimulation were detected by qPCR. (8) The chemoatractant activity of WT or TIARP –/– Neu was tested by transwell chemotaxis assays. (9) To verify the effect of CXCL2 on the chemotactic activity, we performed the chemotaxis assay by applying to the lower chamber with anti-CXCL2 antibody or control IgG. Results: (1) About 80% of aged TIARP –/– mice spontaneously developed arthritis. (2) The severity of arthritis in CIA-TIARP –/– was higher than that in WT. Enhanced infiltration of Neu and Mϕ was observed in joint of TIARP –/– mice. (3) We identified 606 upregulated genes and 1, 010 down-regulated genes in TIARP –/– Neu. Gene ontology (GO) analysis of upregulated genes in TIARP –/– Neu demonstrated the enrichment of genes involved in immune response and chemotaxis. (4) The expression of CXCR1, CXCR2, CCR1 was significantly higher in TIARP –/– Neu. In contrast, CCR3 expression was not different. (5) The expression of TIARP in FLS was significantly increased after TNFα, IL-6 and LPS stimulation. (6) TNFα stimulation induced much more cell proliferation in TIARP –/– FLS than in WT. (7) The expressions of IL-6, TNFα and CXCL2 in TIARP –/– FLS were significantly higher than in WT. However, RANKL, MMP3 and MMP9 expression in TIARP –/– FLS were comparable to WT. (8) The recruitment was enhanced in TIARP –/– Neu compared to those in WT. (9) The numbers of migrated Neu in lower chamber were significantly decreased by the addition of anti CXCL2 antibody. Conclusions: TIARP might down-regulate the production of CXCL2 from FLS and the expression of chemokine receptors (CXCR1 and CXCR2) in Neu, resulting in the protective ability of Neu migration in arthritic joints. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.2770